Violent Movies and Severe Acts of Violence: Sensationalism Versus Science. (14th October 2014) - Markey, Patrick M.; French, Juliana E.; Markey, Charlotte N.
Abstract : Violent media has often been blamed for severe violent acts. Following recent findings that violence in movies has increased substantially over the last few decades, this research examined whether such increases were related to trends in severe acts of violence. Annual rates of movie violence and gun violence in movies were compared to homicide and aggravated assault rates between the years of 1960 and 2012. Time series analyses found that violent films were negatively, although nonsignificantly, related to homicides and aggravated assaults. These nonsignificant negative relations remained present even after controlling for various extraneous variables. Results suggest that caution is warranted when generalizing violent media research, conducted primarily in laboratories and via questionnaires, to societal trends in violent behavior .